Tinjauan Atas Kebijakan Subsidi Public Service Obligation (PSO) Pada PT. PELNI - Sujai, Mahpud (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
As an archipelago state, sea transport services play an important role to connect the Indonesian region from the center and big islands to the remote islands and border area. The importance of sea transport caused the vital role of PT. Pelni as government agent in providing services to the community. As the embodiment of public service, government provide subsidy of public service obligation to PT. Pelni in order to support the operational costs and ease the burden on the community with an affordable tariff determination. This paper explores the problems that occur in line with the PSO subsidy policy for the PT. Pelni. This paper recommends that the PSO subsidy to PT. Pelni given based on the realization of the current year. Another recommendation is the importance of maintaining consistency in the determination of the amount of subsidy based on a predetermined calculation mechanism.Keywords: PT. Pelni, PSO Subsidy, Sea Transportation